NURTURING MARKETING RELATIONSHIPS: THE ROLE OF LOYALTY TENDENCIES BEYOND RELATIONSHIP DYNAMICS - Zaenal Aripin; Ngurah Made Novianha Pynatih; Eko Aristanto (PT. Kreatif Indonesia Satu, 2024)
Maintaining strong marketing relationships with customers is crucial to a company's long-term success. In an era full of intense competition, customer loyalty tendencies have an important role in influencing the dynamics of the relationship between companies and customers. However, customer loyalty tendencies are not only influenced by internal factors, but also by external factors that complicate the dynamics of marketing relationships. This research aims to investigate the role of customer loyalty tendencies beyond the dynamics of marketing relationships. We want to understand how external factors, such as changing market trends and social environmental influences, influence customer loyalty trends, as well as their impact on sustainable marketing relationships. The research method used in this research is qualitative. We conducted an in-depth review of relevant literature, including related journals, articles and books. We also analyzed case studies and previous research to gain comprehensive insight into this topic. The research results show that customer loyalty tendencies play a key role in maintaining sustainable marketing relationships. External factors such as changes in market trends, social environmental influences, and competitors' actions can influence customer loyalty tendencies. It is important for companies to adopt a responsive approach to environmental changes and continuously monitor changes in customer needs and preferences.